A magyarországi régiók humán erőforrás potenciáljának vizsgálata az Európa 2020 stratégia tükrében - Nagy, Henrietta; Káposzta, József (Közép-Európai Közlemények, 2017)
The aim of the paper is to highlight the major tendencies of human resource and employment in the regions of Hungary. The EUROPE 2020 aims to increase the employment rate to 75% and to increase the share of people with diploma, as well as to decrease the share of young population out of schools but unfortunately the tendencies in every day life are totally different. In our study we examined the major statistics in relation with human resource, employment, unemployment and we had to conclude that the regions are not closing the gap but some regions are going into more recession despite of the EU funds used. It is not only the challenge of Hungary but it is a general phenomenon in the Central-Eastern-European region. But it is really important issue because if the human resource is not sufficient to build on, no long-term development strategies can be elaborated successfully in the country. The EU aimed at knowledge-based economic development in the Lisbon Strategy, but if we do not have sufficient labour force, we cannot get out of the recession.